2019
DOI: 10.18268/bsgm2019v71n2a5
|View full text |Cite
|
Sign up to set email alerts
|

The Neolithic variscite mines of Gavà, Catalonia: Criteria for mineral exploration and exploitation in the Prehistory

Abstract: Boletín de la Sociedad Geológica Mexicana / 2019 / 295 RESUMEN El Complejo Minero Neolítico de Gavà (CMNG) ubicado en Cataluña tuvo como objeto la explotación de la variscita verde utilizada para la elaboración de adornos y joyería. Los trabajos arqueológicos en más de 100 minas indican que la minera en este complejo se llevó a cabo ~5800 años antes del presente. CMNG constituye (A) uno de los primeros ejemplos conocidos de minería subterránea en Europa, (B) posiblemente el ejemplo más antiguo de minería a gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Palaeozoic basement lithologies of the central part of the CCR consist of Ordovician, Silurian, Devonian and Carboniferous materials: (1) Ordovician slates and quartzites; (2) Llandoverian sulphide-rich black shales interbedded with centimetre-thick layers of syn-sedimentary apatite and chert; (3) Wenlockian black shales interbedded with centimetric quartzite layers; (4) Ludlowian black shales with interbedded limestone lenses; (5) Pridolian nodular limestones which are partially dolomitised or ankeritised; (6) Lockovian black schists followed by interbedded limestones, reddish shales and green to bluish marls; (7) Lower Carboniferous cherts, greenish shales and greywackes [20][21][22]25,38,43].…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Palaeozoic basement lithologies of the central part of the CCR consist of Ordovician, Silurian, Devonian and Carboniferous materials: (1) Ordovician slates and quartzites; (2) Llandoverian sulphide-rich black shales interbedded with centimetre-thick layers of syn-sedimentary apatite and chert; (3) Wenlockian black shales interbedded with centimetric quartzite layers; (4) Ludlowian black shales with interbedded limestone lenses; (5) Pridolian nodular limestones which are partially dolomitised or ankeritised; (6) Lockovian black schists followed by interbedded limestones, reddish shales and green to bluish marls; (7) Lower Carboniferous cherts, greenish shales and greywackes [20][21][22]25,38,43].…”
Section: Geological Settingmentioning
confidence: 99%
“…Minerals 2020, 10, 3 3 of 25 chert; (3) Wenlockian black shales interbedded with centimetric quartzite layers; (4) Ludlowian black shales with interbedded limestone lenses; (5) Pridolian nodular limestones which are partially dolomitised or ankeritised; (6) Lockovian black schists followed by interbedded limestones, reddish shales and green to bluish marls; (7) Lower Carboniferous cherts, greenish shales and greywackes [20][21][22]25,38,43]. During the Hercynian orogeny, the Palaeozoic series was affected by two generations of tight folds roughly trending NW-SE but with opposite vergence.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The geological study of most of the iron mines was performed as the archeological excavations progressed. This aspect was important in order to discriminate between the Neolithic variscite mines (see Díaz-Acha et al, 2019) and more recent iron mines, especially where both types of mines occur nearby each other. Both artisanal and industrial mineral operations can be recognized in Gavà.…”
Section: Distribution Of Iron Mining Operations In the Gavà Areamentioning
confidence: 99%
“…The Gavà area is famous worldwide for the existence of ancient Neolithic mines (Alonso et al, 1978;Villalba et al, 1986Villalba et al, , 1989Villalba et al, , 1990Camprubí et al, 1994Camprubí et al, , 2003Costa et al, 1994;Bosch et al, 1996;Villalba, 2002;Díaz-Acha et al, 2019) and the important archeological objects found therein, such as the Gavà Venus (Bosch and Estrada, 1994) and variscite ornaments (Borrell and Estrada, 2009). However, many other types of mining operations for iron exist in the same area, in many cases in the immediate vicinity of the Neolithic works and separated from them by only tens of meters.…”
Section: Introduction / Geological Backgroundmentioning
confidence: 99%